Assessment of Relationship Between Sleep Disordered Breathing and Angle’s Molar Relationship in Children between Age Group Of 8-13 Years – A Cross-Sectional Study - Dr. Kirti Shukla; Dr. Bhavna Dave; Dr. Seema Bargale; Dr. Anshula Deshpande; Dr. Poonacha K S; Dr. Pratik Kariya (The Bioscan, 2025)
Aim: To assess sleep related breathing disorders through screening questionnaire and the association of Sleep Disordered Breathing (SDB) with Angle’s molar relationship in permanent dentition in 8 to 13 year old children. Materials and Methods: 103 children aged 8 to 13 years reporting to the department were assessed for SDB and Angle’s classification of malocclusion. Their parents were administered a pre-validated Pediatric Sleep Questionnaire (PSQ) for assessing SDB, by a single, calibrated examiner. The primary outcomes were SDB score and Angle class of malocclusion. Results: The sample of the study consisted of a total of 103 children in the age group of 8–13 years with 55 (53.40%) males and 48 (46.60%) females. Most of the children were between the age group of 9-11 years (49 children). In the assessment of dental variables in the anteroposterior direction, the most common molar relationship was found in Class I (66%) in all children, followed by Class II (34%) and Class III (3%). Out of 103 study subjects, 69 had Snoring Problems. Conclusion: An association exists between malocclusion and Sleep Disordered Breathing in children. Dental evaluations may serve as a preliminary screening tool for identifying children at risk for SDB.